The Impact of the Interest Rate on Industrial Production During the 2008 Financial Crisis and the COVID-19 Pandemic - Köse, Nezir; Ünal, Emre (My University, 2024)
The impact of the real interest rate on industrial production growth in developed and developing countries was analyzed during the 2008 financial crisis and the COVID-19 pandemic. Panel data analysis was implemented for the monthly period between January 2002 and December 2020. The impact of the real interest rate on industrial production growth was negative for both developed and developing countries in all periods. Moreover, during the 2008 financial crisis, the relationship between the real interest rate and industrial production growth was negative for both developed and developing countries. However, the effect of the real interest rate was stronger in developed countries. During the COVID-19 pandemic, the impact of the real interest rate on industrial production growth has been much stronger than that of the 2008 financial crisis. Its effect has also been more significant in developed countries. The result indicates that during the crisis and the pandemic, a decrease in the real interest rate plays an important role in stimulating industrial production. Pulling the real interest rate down can be an effective tool for promoting growth and can lessen negative consequences in economic activities during the COVID-19 pandemic. Nevertheless, as the inflation rate is very low in developed countries, the risk of depreciation in the exchange rate in developing countries can be limited following expansionary monetary policy. Hence, other alternatives such as government intervention into economic activities by fiscal policy increase in importance beside monetary policy.
Keywords: Panel data analysis; COVID-19 pandemic; interest rate; industrial production; 2008 financial crisis